2002
DOI: 10.3750/aip2002.32.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival of rohu, Labeo rohita (Hamilton) spawn fed diets supplemented with fish intestinal microflora

Abstract: A 21-day feeding experiment was conducted to assess the effects of diets supplemented with fish intestinal bacteria producing extracellular enzyme on growth and survival of rohu, Labeo rohita (Hamilton) spawn (average weight 0.3 mg). Intestinal bacteria were isolated from healthy rohu fingerlings s averag � w � ight 3.51 _ ±0.31 _ g). Six isocaloric (4.24 kcal·g-) and 1somtrogenous \approximately 35% crude protein) diets (Dl-D6) were prepared containing 32% fish meal, 34% mustard oil cake, 30% rice bran, 2o/o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 15 publications
3
30
0
Order By: Relevance
“…Similar to these results, Ghosh et al in 2004 confirmed that bacillus cerculance isolated from intestine of fish species, Labeo rohita, at the level equal to 2  10 8 CFU feed, Changed the weight of fry from 3.45 to 4.61g [21]. According to these results, Ghosh et al in 2002 showed that bacillus isolated from intestine of labeo rohita fish has more effect on increased weight of larvae of this fish than commercial bacillus [12,13].…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Similar to these results, Ghosh et al in 2004 confirmed that bacillus cerculance isolated from intestine of fish species, Labeo rohita, at the level equal to 2  10 8 CFU feed, Changed the weight of fry from 3.45 to 4.61g [21]. According to these results, Ghosh et al in 2002 showed that bacillus isolated from intestine of labeo rohita fish has more effect on increased weight of larvae of this fish than commercial bacillus [12,13].…”
Section: Discussionsupporting
confidence: 76%
“…In Microbial management, native species isolated from aquatic digestive tract, have played important roles in aquaculture purposes. Similar research were done by Ghosh et al in 2002 with Bacillus circulans isolated from intestine of fish species, Labeo rohita, in diets supplemented with them [12,13]. Also, bacteria Lactobacillus fructivorans isolated from fish species, Sparus auratus, as well as Lactobacillus plantarum (L. plantarum) isolated from human feces, led to increased growth and survival of this fish, after supplementation with Artemia franciscana nauplii [14].…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations